The Role of Leadership Style in Improving Administrative Efficiency: A Comparative Study of Public and Private Institutions - Muhammad Natsir Mallawi; Nurasia Natsir (International Journal of Economics, Commerce, and Management, 2026)
Leadership constitutes a critical determinant of organizational efficiency, yet the relationship between leadership styles and administrative effectiveness remains incompletely understood, particularly across different institutional contexts. This comparative study examines how transformational, transactional, and laissez-faire leadership styles influence administrative efficiency in public and private sector institutions in Indonesia. Using a mixed-methods approach, quantitative data were collected from 428 employees across 28 public institutions and 24 private organizations through validated survey instruments; qualitative data were gathered through 36 semi-structured interviews with organizational leaders and managers. Results reveal significant positive relationships between transformational leadership and administrative efficiency in both sectors (β = 0.54, p < 0.001 for public; β = 0.48, p < 0.001 for private), with transactional leadership showing moderate positive effects (β = 0.32 public; β = 0.38 private) and laissez-faire leadership demonstrating negative relationships (β = −0.28 public; β = −0.24 private). Leadership styles collectively explain 52% of efficiency variance. Mediation analysis reveals that organizational culture (28%), employee engagement (35%), and trust in leadership (22%) partially mediate transformational leadership's effects, together accounting for 62% of total indirect effects. Sector differences emerged qualitatively: transformational leadership leverages public service motivation in public institutions, while transactional leadership's performance accountability resonates more strongly in private organizations. The study contributes theoretical understanding of leadership effectiveness across institutional contexts and provides practical guidance for developing contextually appropriate leadership development programs.